Grasping de(centralized) fi(nance) through the lens of economic theory - Jonathan Chiu; Thorsten V. Koeppl; Charles M. Kahn (Queen's University, Department of Economics, 2022)
In this viewpoint article, we provide an analysis of the value proposition of De(centralized) Fi(nance) and its limitations using a simple stylized model of collateralized lending. DeFi uses a decentralized ledger to run smart contracts that automatically enforce the terms of a lending contract and safeguard the collateral. DeFi can lower the costs asso- ciated with intermediated lending and improve financial inclusion. Limitations are the volatility of crypto collateral and stablecoins used for settlement, the possible incom- pleteness of smart contracts and the lack of a reliable oracle. A proper infrastructure reducing such limiations could improve the value of DeFi.
Keywords: G2; 330; Decentralized Finance; Cryptocurrency; Stablecoins; Collateralized Lending; Virtuelle Währung; Kreditgeschäft; Kreditrationierung; Kreditmarkt; Theorie